PJMHS 2021
DOI: 10.53350/pjmhs2115102685
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Effectiveness of Letrozole Versus Clomiphene Citrate to Evaluate the Ovulation Induction in patients with POS

Abstract: Background: Anovulation is the commonest cause of female infertility and polycystic ovarian syndrome (PCOS) is the most frequently seen cause of anovulation among infertile females. Letrozole and Clomiphene Citrate are two common drugs for PCOS. But controversial data was noticed regarding their effectiveness. Aim: To compare effectiveness of Letrozole versus Clomiphene Citrate to evaluate the ovulation induction in patients with polycystic ovarian syndrome Methods: After fulfilling the selection criteria, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…S15 Fig. Risk of bias assessment of the studies included in the meta-analysis assessing endometrial thickness (ET) [1, 4, 5, 16, 19, 41, 4346, 56] using the revised tool for assessing risk of bias in randomized trials (Rob 2). Legend: +: low risk; !…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…S15 Fig. Risk of bias assessment of the studies included in the meta-analysis assessing endometrial thickness (ET) [1, 4, 5, 16, 19, 41, 4346, 56] using the revised tool for assessing risk of bias in randomized trials (Rob 2). Legend: +: low risk; !…”
Section: Supporting Informationmentioning
confidence: 99%
“…S16 Fig. Risk of bias assessment of the studies included in the meta-analysis assessing endometrial thickness (ET) [1, 4, 5, 16, 19, 41, 4346, 56] broken down to tools, shown in percentage.…”
Section: Supporting Informationmentioning
confidence: 99%